Pengaruh Financial Technology Terhadap Perbankan Syariah: Pendekatan ANP-BOCR (The Influence of Financial Technology on Islamic Banking: ANP-BOCR Approach) - Muhammad, Helmi; Sari, Niki Puspita (Universitas Muhammadiyah Sidoarjo, 2020)
The objective of this study was to examine the influence of financial technology (FinTech) on Islamic banking from the aspects of benefit, opportunity, cost and risk (BOCR). The research data were obtained through in-depth interviews and questionnaires from respondents which consisted of experts from academia, FinTech practicioners, Islamic banking practitioners and financial services authorities who were chosen by purposive sampling. The data analysis method of this research was Analytical Network Process (ANP) with the BOCR network structure approach. The results show that based on the priority aspects of the respondents' answers, rapid development of the FinTech industry provides positive opportunities for Islamic banking to implement strategic cooperation with the FinTech industry as a customer-oriented integral part.